Diversity and spatial pattern of ground-dwelling ants in different habitat types, Kalabakan, Sabah - Muhammad Afif Zakaria (2014)
Conversion of natural forests often leads to serious damage such as forest fragmentation, forest degradation as well as loss of total habitat which eventually leads to significant loss of biodiversity. Ants can be good bio-indicators due to their abundance, diversity and sensitivity to environmental changes. Logging activities can alter the structure of ant communities where forest specialists are more abundant in undisturbed habitat compared to disturbed habitat. A study of ant species composition in different habitats was conducted in the Stability of Altered Forest Ecosystem (SAFE) experimental sites and its surrounding areas in Sabah. This study investigates (i) difference in species richness and abundance of ant in different habitats, (ii) the effects of environmental variables on ant assemblage, (iii) species similarity and indicator species of each habitat and (iv) ant spatial distribution and species co-occurrence in local spatial scale. Ants were collected along 200m line transects according to the Ants of Leaf Litter (ALL) Protocol from old growth forest (OG), logged forest (LF) and oil palm (OP) plantation areas. Environmental variables namely forest quality, soil pH and temperature, low vegetation, canopy cover, humidity, abundance of liana, and leaf litter depth were collected. A total of 174 species belonging to 64 genera in twelve subfamilies were recorded in this study. Species richness was significantly higher in OG (121) than in LF (105) and OP (70) (ANOVA, df=2, F=89.869, p<0.001). Canonical Correspondence Analysis (CCA) showed that air temperature, canopy cover, abundance of low vegetation, abundance of liana, soil pH, forest quality and litter depth influenced the ants’ assemblage. Many species of ants such as Strumigenys sp.1, Ponera sp.3 and Hypoponera sp.1 were associated with environmental parameters characterising the OG (high canopy cover, leaf litter depth, soil pH, abundance of liana and forest quality). Lophomyrmex bedoti and Crematogaster sp.2 on the other hand were observed associate with low forest quality, low vegetation cover and high air temperature of OP. There are five potential species selected as biological indicator for each habitat except LF. Lophomyrmex bedoti was an indicator species for OP while Strumigenys sp.1, Acropyga sp.1, Carebara sp.1 and Ponera sp.2 were indicator species for OG. Null model analysis of species co-occurrence showed the observed C-score index has insignificant difference with simulated C-score index for all habitats. The ants’ spatial distribution in this study is not structured by the non-random pattern of species co-occurrence. Here we can conclude that the diversity and species composition of ground-dwelling ants were different across habitat types. The differences in vegetation structure of each habitat resulting in changes to environmental conditions which directly influence ant species assemblage. Preserving the old growth forest and logged forest are indeed important since both habitats still can harbour high number of ant species. In contrast, oil palm plantation is not capable of serving as refuge for grounddwelling forest ants.